Big Book Integration in ARIAS Learning Model to Improve Elementary School Students' Storytelling Ability - Lestari Jumadi, Putri; Krismanto, Wawan; Ilmi, Nur (Journal of Classroom Action Research, 2025)
Low storytelling ability is still one of the problems in language learning. Therefore, this study describes the process and results of implementing actions in the form of Big Book media integration in the ARIAS learning model to improve students' storytelling ability. The research approach is qualitative, with the type of classroom action research. The study subjects were teachers and 22 UPTD SD Negeri 81 Parepare, South Sulawesi third-grade students. Data collection techniques were in the form of observation, storytelling skills tests, and documentation. The research instruments were observation sheets and storytelling skills assessment sheets. Data was analyzed through condensation, presentation, and conclusion or verification. The study results showed that integrating Bigbook in the ARIAS learning model helped students be involved in the learning process because they actively practiced reading and storytelling individually and in groups with the help of visualizations in the Bigbook. Changes in the process led to increased storytelling ability; in the first cycle, only 31% of students were in the Good category, and in the second cycle, the remaining 14% were still in the Sufficient and Fewer categories. This study concludes that integrating the Bigbook into the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) learning model can improve students' storytelling ability.